Declining populations of greater sage‐grouse: hunter motivations when numbers are low. (20th May 2015) - Guttery, M. R.; Messmer, T. A.; Brunson, M. W.; Robinson, J. D.; Dahlgren, D. K.
Abstract: As a hunted species becomes increasingly rare, the effort required to locate and harvest an individual tends to increase. As rarity increases, governmental oversight, including changes in hunting regulations and protection of habitats and individuals using mechanisms such as the US Endangered Species Act (ESA), can be used to mitigate extinction risks. However, recent research has demonstrated the existence of a feedback mechanism through which increased rarity may increase hunter demand for opportunities to pursue rare species before the opportunity is lost. This phenomenon, referred to as the anthropogenic Allee effect, may exacerbate exploitation, thereby resulting in disproportionally large effects of harvest on vulnerable species. In 2010, the US Fish and Wildlife Service designated greater sage‐grouse ( C entrocercus urophasianus ; sage‐grouse) as a candidate for listing under the ESA. Although sage‐grouse are a candidate for ESA listing, they are still hunted throughout much of their current range. In 2008, the demand for sage‐grouse hunting permits in Utah exceeded their availability, raising questions about why hunters choose to pursue this species. We hypothesized that the pending ESA listing decision increased hunter demand for permits. We surveyed randomly selected hunters who obtained permits to hunt sage‐grouse in Utah in 2008–2010 ( n  = 838) to determine their motivations for hunting sage‐grouse and determinants of hunter satisfaction. The most commonly reported reasons for hunting sage‐grouse were to spend time with family, for tradition and meat. Although the potential ESA listing was not a major motivational factor in 2009 or 2010, the percentage of respondents selecting this option did increase by 7%. Hunter awareness of the ESA listing petition also increased by 18% during this period. Our results provide new insights on the sociological importance and potential threats of hunting rare species.